Advances in protective structures research : proceedings of the IAPS Open Forum on Recent Research Advances on Protective Structures, Tianjin, China, 13-14 September 2012 /: proceedings of the IAPS Open Forum on Recent Research Advances on Protective Structures, Tianjin, China, 13-14 September 2012. (©2012) - Unknown
No abstract available